Autonomia e discricionariedade do Ministério Público no Brasil - Kerche,Fábio (2007)
This article deals with the autonomy, discretionary power, and wide range of attributions allotted to the Public Prosecutor's Office in Brazil by the 1988 Constitution. One of the objectives is to analyze whether this combination is not alien to the democratic principle that state institutions, and even those that do not choose their members by direct elections, should be accountable to the public for their acts. The author draws on the neo-institutionalist literature on bureaucracy to analyze the Public Prosecutor's Office in Brazil. The conclusion is that there has been a quasi-abdication by politicians in relation to the institution in question, a rare occurrence in Brazil and in other democracies.